The Saxon War - Bruno, of Magdeburg, active 1084 (Book collections on Project MUSE., 2022)
"Bruno, a cleric who served the archbishop of Magdeburg and subsequently the bishop of Merseburg during the course of the 1060s to the 1080s, composed one of the most important historical works treating the tumultuous period in the history of the German kingdom in the second half of the eleventh century. Bruno's main focus in his Saxon War is the civil wars that engulfed the German kingdom from the mid 1060s through the end of the 1080s, and he treats military manners in a very detailed manner. Bruno was closely connected to the foremost leaders of the Saxon resistance against King Henry IV, and provides unique insights regarding their plans, hopes, and fears. Bruno also provides nearly two dozen full-text copies of letters that were sent by the main participants in the intra-German conflict as well as ten letters from Pope Gregory VII. Bruno also offers insights regarding the so-called Investiture Controversy. This will be the first English translation of this work"--